Oil industry waste: a potential feedstock for biodiesel production. Issue 16 (17th August 2016) - Abbas, Javeria; Hussain, Sabir; Iqbal, Muhammad Javid; Nadeem, Habibullah; Qasim, Muhammad; Hina, Saadia; Hafeez, Farhan
ABSTRACT: The worldwide rising energy demands and the concerns about the sustainability of fossil fuels have led to the search for some low-cost renewable fuels. In this scenario, the production of biodiesel from various vegetable and animal sources has attracted worldwide attention. The present study was conducted to evaluate the production of biodiesel from the oil industry waste following base-catalysed transesterification. The transesterification reaction gave a yield of 83.7% by 6:1 methanol/oil molar ratio, at 60°C over 80 min of reaction time in the presence of NaOH. The gas chromatographic analysis of the product showed the presence of 16 fatty acid methyl esters with linoleic and oleic acid as principal components representing about 31% and 20.7% of the total methyl esters, respectively. The fourier transform infrared spectroscopy spectrum of oil industry waste and transesterified product further confirmed the formation of methyl esters. Furthermore, the fuel properties of oil industry waste methyl esters, such as kinematic viscosity, cetane number, cloud point, pour point, flash point, acid value, sulphur content, cold filter plugging point, copper strip corrosion, density, oxidative stability, higher heating values, ash content, water content, methanol content and total glycerol content, were determined and discussed in the light of ASTM D6751 and EN 14214 biodiesel standards. Overall, this study presents the production of biodiesel from the oil industry waste as an approach of recycling this waste into value-added products.